Working conditions in Ghana's export processing zone and women's empowerment. (1st December 2015) - ,; ,; ,
Abstract : Globalisation and the spread of export processing zones (EPZs) have created new opportunities in Ghana for women to obtain paid work. However, the empowering effects of this employment are quite poorly understood. This article examines the relationship between working conditions in EPZs and the empowerment of women. Although EPZs are globally depicted as characterised by harsh working conditions which militate against women's empowerment, the situation in Ghana is relatively better and this type of employment has enhanced the economic and psychological well-being of some women. However, the insecurity of jobs in the EPZs is a major hindrance to their empowerment.